Bulb selection of shallot local varieties from true shallot seeds (TSS) for bulb split components - Linda Nursalma; Awang Maharijaya; Sobir (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
The development of quality shallot seeds from new superior varieties needs to be done because only about 10% of the shallot seed needs are currently covered. However, true shallot seeds (TSS) production from the local varieties, such as the Bima Brebes variety, is still rarely developed and has not been able to produce many split bulbs from TSS. The existence of split bulbs in one plant is preferred by consumers and is beneficial for shallot seedlings. This is related to the number of seeds farmers can use per kilogram of seed obtained. Therefore, this study aimed to select shallots that produce split bulbs from seeds produced from TSS. This research was conducted at Tajur Experimental Farm, Center for Tropical Horticulture Studies IPB University, Bogor. Seedlings were done in beds shaded with transparent plastic that can be opened and closed. The split bulbs produced by the Bima Brebes variety derived from TSS seed sources were still relatively low at 39.69% and significantly different from the comparison varieties at more than 60%. Sanren variety produced split bulbs from TSS seed sources as high as 64.13% and the Maserati variety about 61.25%. Keywords: spit bulb; dry weight; fresh weight; true shallot seed